The Effect of Job Insecurity, Organizational Virtuousness to Subjective Well-being, Organizational Commitment, Organizational Citizenship Behavior, and Job Performance - Muhamad Nurrohman; Unggul Kustiawan (HK-Publishing, 2022)
AbstractThe purpose of this research is to explain the connection between job insecurity and organizational virtuousness to work-family conflict, organizational identification, subjective well-being, organizational commitment, organizational citizenship behavior, and job performance. The sample for this research comprises employees working in manufacturing companies in Industrial areas of Banten Province, Indonesia, and those who have worked for more than two years. The sampling is done using purposive sampling with the total number for the sample being 220 and the gathering data using survey method by giving an online questionnaire. To analyze data is using factor analysis and Lisrel Structural Equation Model (SEM), and the findings of the study have proved that job insecurity positively affects subjective well-being, work-family conflict, and organizational identification. On the other hand, organizational identification negatively affects organizational citizenship behavior and job performance. Furthermore, organizational virtuousness positively affects subjective well-being. Subjective well-being positively affects organizational commitment. Also, organizational commitment effects positively to organizational citizenship behavior and job performance. However, subjective well-being effects negatively to job performance.Keywords: job insecurity, subjective well-being, organizational virtuousness, organizational citizenship behavior, job performance. AbstrakTujuan dari penelitian ini adalah untuk menjelaskan hubungan antara job insecurity dan virtuousness organisasi terhadap konflik pekerjaan-keluarga, identifikasi organisasi, kesejahteraan subjektif, komitmen organisasi, perilaku kewargaan organisasi, dan prestasi kerja. Sampel dalam penelitian ini adalah karyawan yang bekerja pada perusahaan manufaktur di Kawasan Industri Provinsi Banten, Indonesia, dan yang sudah bekerja lebih dari 2 tahun. Pengambilan sampel dilakukan dengan menggunakan purposive sampling dengan jumlah sampel 220 orang dan pengumpulan data menggunakan metode survei dengan memberikan kuesioner online. Analisis data menggunakan analisis faktor dan Lirel Structural Equation Model (SEM) dimana temuan penelitian telah membuktikan bahwa ketidakamanan kerja mempengaruhi kesejahteraan subjektif positif, konflik pekerjaan-keluarga, dan identifikasi organisasi. Identifikasi organisasi mempengaruhi perilaku kewargaan organisasi dan kinerja pekerjaan secara negatif. Selanjutnya, kebajikan organisasi mempengaruhi kesejahteraan subjektif positif. Kesejahteraan subjektif berpengaruh positif terhadap komitmen organisasi. Juga, komitmen organisasi berpengaruh positif terhadap perilaku kewargaan organisasi dan kinerja pekerjaan. Namun, kesejahteraan subjektif berpengaruh negatif terhadap prestasi kerja.Katakunci:ketidakamanan kerja, kesejahteraan subjektif, kebajikan organisasi, perilaku kewarganegaraan organisasi, kinerja pekerjaan.